Obesity/ies: bodies, foods and inequalities - Salas Valenzuela, Monserrat; Castañeda Salgado, Martha Patricia (INTER DISCIPLINA, 2021)
Recognizing that there is no absolute consensus on the issue of obesity, we continue to ask ourselves how to approach it without leaving anything aside, without privileging only one point of view, without closing our eyes to so many others. For the moment, we decided to offer this thematic number so that the set of texts allow those who read them to broaden their point of view, hopefully question their own and above all, contribute to continue the discussion. In an attempt to order the conversation, we will emphasize three axes that in our opinion cross the problem of the so–called obesity, contributing with questions and questions, although without yet offering all the answers.